Case Report: Identification of a Novel GNAS Mutation and 1p/22q Co-Deletion in a Patient With Multiple Recurrent Meningiomas Sensitive to Sunitinib - Hong, Weiping; Shan, Changguo; Ye, Minting; Yang, Yanying; Wang, Hui; Du, Furong; Zhang, Xing; Song, Chao; Cai, Linbo (Frontiers in Oncology, 2021)
Background: Although surgical resection can cure the majority of meningiomas, there are still approximately 20% of patients suffering from an aggressive course with recurrence or progression. In this study, we reported a novel GNAS mutation and 1p/22q co-deletion responding to sunitinib in a patient with multiple recurrent meningiomas. Case presentation: A 53-year-old woman was hospitalized due to tumor progression for 3 weeks after 4 times of meningioma surgeries. WHO grade I meningioma was pathologically diagnosed after the first three surgeries, but the second recurrence occurred approximately 3 years following the third surgery. Next-generation sequencing was performed on the first two recurrent samples. GNAS mutations and 1p/22q co-deletion were both identified, and amplification at 17q and chromosome 19 was also found in the second recurrent sample, based on which WHO grade II/III meningioma was diagnosed. The lesion in the left cerebellopontine angle area enlarged after 2-month use of radiotherapy combined with temozolomide chemotherapy, then sunitinib was added, the residual lesions lessened after two months and significantly reduced after use of 8 months. Conclusion: This typical case suggested that timely molecular diagnosis for refractory meningiomas was conductive to guiding the molecular classification and directing clinicians to make more reasonable individualized therapeutic regimens for patients, consequently benefiting from the therapies. This case report also highlighted the potential role of sunitinib in the treatment of refractory meningiomas.